Diversity and Distribution of Herpetofauna in Banyu Nibo Waterfall Ecotourism Region, Nglanggeran, Gunung Kidul, Special Region of Yogyakarta - Alfonsus Toribio Eko Saputro; Elika Boscha; Ananto Puradi Nainggolan; Donan Satria Yudha; Rury Eprilurahman (Universitas Gadjah Mada, 2020)
Banyu Nibo Waterfall is located near Nglanggeran, Gunung Kidul that well known for its eco-tourism development. The geographical and ecosystem condition could be providing unique habitat for herpetofauna. Herpetofauna has important role in the ecosystem as food chain components and even as environment bioindicator.The aim of this research is to asses the herpetofauna diversity in Banyu Nibo Waterfall as preliminary biodiversity data. The research was conducted using VES (Visual Encounter Survey) assisted by 500 meters transect line. As a result, 15 species were found, mainly distributed on area with tree coverage.